2023
DOI: 10.1001/jamanetworkopen.2022.53806
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antimicrobial Stewardship Programs and Antibiotic Use Globally

Abstract: ImportanceAntimicrobial resistance continues to spread rapidly at a global scale. Little evidence exists on the association of antimicrobial stewardship programs (ASPs) with the consumption of antibiotics across health care and income settings.ObjectiveTo synthesize current evidence regarding the association between antimicrobial stewardship programs and the consumption of antibiotics globally.Data SourcesPubMed, Web of Science, and Scopus databases were searched from August 1, 2010, to Aug 1, 2020. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 80 publications
1
52
0
Order By: Relevance
“…Of note, AMS was shown to be effective in reducing antibiotic consumption in both hospital and nonhospital settings in a recent systematic review and meta-analysis. 52 Other studies showed the feasibility of implementing effective AMS interventions during the COVID-19 pandemic in healthcare settings. 53,54 Our data showed an upward trend in the hospital-based use of coamoxiclav (amoxicillin/clavulanic acid) during all waves of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, AMS was shown to be effective in reducing antibiotic consumption in both hospital and nonhospital settings in a recent systematic review and meta-analysis. 52 Other studies showed the feasibility of implementing effective AMS interventions during the COVID-19 pandemic in healthcare settings. 53,54 Our data showed an upward trend in the hospital-based use of coamoxiclav (amoxicillin/clavulanic acid) during all waves of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important that the AMR/ antimicrobial consumption (AMC) targets are revisited and attention to the matter is amplified. Of note, AMS was shown to be effective in reducing antibiotic consumption in both hospital and nonhospital settings in a recent systematic review and meta‐analysis 52 . Other studies showed the feasibility of implementing effective AMS interventions during the COVID‐19 pandemic in healthcare settings 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial stewardship programs are associated with a reduced proportion of antibiotic prescriptions 19 . There are conflicting results in the literature about the effect of education on prescription practices.…”
Section: Discussionmentioning
confidence: 99%
“…Without an appropriate measure, this may increase to 10 million deaths annually by 2050 [ 81 ]. ASP, as a measure within the One Health transdisciplinary action, decreased the consumption of antibiotics by up to 28% [ 82 ]. Moreover, implementing ASP using a multidisciplinary approach for PK/PD analysis reduced the rate of MDR in ICU-acquired infections by almost 9% [ 83 ].…”
Section: Discussionmentioning
confidence: 99%